PENINGKATAN KOMPETENSI ASN MELALUI SISTEM INFORMASI SUMBER DAYA MANUSIA, PENGEMBANGAN KARIER DAN DISIPLIN KERJA ASN, SERTA DAMPAKNYA TERHADAP KINERJA ASN DI INSTANSI PEMERINTAH KOTA MEDAN - Panjaitan, Ferry; Sianipar, Gloria (UNIKA Santo Thomas, 2017)
Abstract The purpose of this research is to know the improvement of ASN competence through human resource information system, career development and work discipline of ASN, and its impact on ASN performance in Medan city government institution. Analytical technique used in hypothesis test in this research used Structural Equation Modeling (SEM). This study uses secondary data in the form of recapitulation of ASN amount spread over various SKPD in Medan City Government and primary in the form of questionnaires distributed to ASN spread on various SKPD existing in Medan City Government. Population or Total ASN in Medan City Government as many as 5,384 people from population taken sample of 373 ASN by Proportionate Stratified Random Sampling. The result of research in Medan City Government shows the implementation of Human Resource Information System has a positive and significant impact on ASN career development, the implementation of human resource information system has a positive and significant impact on ASN discipline, ASN work discipline has significant influence on ASN competence, Human, discipline and career development have no significant effect on ASN performance, competence mediate the influence of career development on ASN performance, competence able to mediate relationship or influence discipline on ASN performance, Competence has significant influence to ASN performance